FcγRIIIb Restricts Antibody-Dependent Destruction of Cancer Cells by Human Neutrophils - Treffers, Louise W.; van Houdt, Michel; Bruggeman, Christine W.; Heineke, Marieke H.; Zhao, Xi Wen; van der Heijden, Joris; Nagelkerke, Sietse Q.; Verkuijlen, Paul J. J. H.; Geissler, Judy; Lissenberg-Thunnissen, Suzanne; Valerius, Thomas; Peipp, Matthias; et al. (Frontiers in Immunology, 2019)
The function of the low-affinity IgG-receptor FcγRIIIb (CD16b), which is uniquely and abundantly expressed on human granulocytes, is not clear. Unlike the other Fcγ receptors (FcγR), it is a glycophosphatidyl inositol (GPI) -anchored molecule and does not have intracellular signaling motifs. Nevertheless, FcγRIIIb can cooperate with other FcγR to promote phagocytosis of antibody-opsonized microbes by human neutrophils. Here we have investigated the role of FcγRIIIb during antibody-dependent cellular cytotoxicity (ADCC) by neutrophils towards solid cancer cells coated with either trastuzumab (anti-HER2) or cetuximab (anti-EGFR). Inhibiting FcγRIIIb using CD16-F(ab’)2 blocking antibodies resulted in substantially enhanced ADCC. ADCC was completely dependent on FcγRIIa (CD32a) and the enhanced ADCC seen after FcγRIIIb blockade therefore suggested that FcγRIIIb was competing with FcγRIIa for IgG on the opsonized target cells. Interestingly, the function of neutrophil FcγRIIIb as a decoy receptor was further supported by using neutrophils from individuals with different gene copy numbers of FCGR3B causing different levels of surface FcγRIIIb expression. Individuals with one copy of FCGR3B showed higher levels of ADCC compared to those with two or more copies. Finally, we show that therapeutic antibodies intended to improve FcγRIIIa (CD16a)-dependent natural killer (NK) cell ADCC due to the lack of fucosylation on the N-linked glycan at position N297 of the IgG1 heavy chain Fc-region, show decreased ADCC as compared to regularly fucosylated antibodies. Together, these data confirm FcγRIIIb as a negative regulator of neutrophil ADCC towards tumor cells and a potential target for enhancing tumor cell destruction by neutrophils.